1988
DOI: 10.1111/j.1476-5381.1988.tb16572.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance P, neurokinin A and neurokinin B in the ocular response to injury in the rabbit

Abstract: 1 Substance P (SP) and neurokinin A-(NKA)/neurokinin B (NKB)-like immunoreactivity (LI) were measured by radioimmunoassay in extracts of the rabbit uvea. The iris-ciliary body complex contained 3-4 times more NKA/NKB-LI than SP-LI. Tachykinins are thought to mediate many of the responses to ocular injury in the rabbit. Their possible role in the miosis and breakdown of the blood-aqueous barrier (BAB) was studied in vitro and in vivo. 2 In vitro, NKA had a more short-lasting contractile effect on the sphincter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 22 publications
(28 reference statements)
2
22
0
Order By: Relevance
“…In fact, SP is likely to be responsible for at least a part of the capsaicinevoked secretion because capsaicin was shown to release SP from such fibres in the nasal mucosa, in agreement with the findings by Lundblad et al (1985), and an antagonist of SP, (D-Pro2,D-Trp7' 9)_ SP, inhibited the capsaicin-evoked secretion in the present study. Antagonists of SP also antagonize other tachykinins, such as neurokinin A (NKA) (Beding-Barnekow et al, 1988). NKA occurs together with SP in sensory nerve fibres in the nasal mucosa (Sundler et al, 1985) and may be responsible for some of the effect of capsaicin.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, SP is likely to be responsible for at least a part of the capsaicinevoked secretion because capsaicin was shown to release SP from such fibres in the nasal mucosa, in agreement with the findings by Lundblad et al (1985), and an antagonist of SP, (D-Pro2,D-Trp7' 9)_ SP, inhibited the capsaicin-evoked secretion in the present study. Antagonists of SP also antagonize other tachykinins, such as neurokinin A (NKA) (Beding-Barnekow et al, 1988). NKA occurs together with SP in sensory nerve fibres in the nasal mucosa (Sundler et al, 1985) and may be responsible for some of the effect of capsaicin.…”
Section: Resultsmentioning
confidence: 99%
“…The eyes were immediately taken out. The iris was cut in half and the two halves were mounted in separate tissue baths (37°C), containing 8 ml of modified Krebs solution (Beding-Barnekow et al, 1988). The solution was bubbled continuously with 93% 02 and 7% C02, giving a pH of 7.4.…”
Section: Generalmentioning
confidence: 99%
“…This concentration of capsaicin was chosen to produce approximately 50% of the maximal response (Wang & Hakanson, 1992a). After the capsaicin-induced contraction had reached its maximum (usually within 10min), the preparation was washed with drug-free Krebs solution and allowed to rest for 1 h. The preparation was then exposed to a buffer solution containing 137.7mM KCI (but no NaCI) (Beding-Barnekow et al, 1988); the resulting contraction was used as an internal standard. Each preparation was exposed to one concentration of ruthenium red or capsazepine only.…”
Section: Generalmentioning
confidence: 99%
“…On the basis of pharmacological analysis, Ueda et al (11) and Muramatsu et al (12) have proposed that NKA rather than SP is a possible transmitter for mediating such a contraction. Beding-Barnekow et al (8) have suggested that ETS of rabbit iris sphincter muscle results in simultaneous release of SP and NKA.…”
mentioning
confidence: 99%
“…It has also been demonstrated that other members of the tachykinin family such as neurokinin A (NKA) and neurokinin B (NKB) are present in the iris sphincter mus cle of rabbits (7,8). Electrical transmural stimulation (ETS) of the isolated rabbit iris sphincter muscle pro duces a noncholinergic, nonadrenergic contraction that is inhibited by tetrodotoxin and tachykinin antagonists (2,(9)(10)(11)(12).…”
mentioning
confidence: 99%